033 Cluster of creuzfeldt-jakob disease in the south western sydney local health district population in the past 5 years. (29th July 2019) - Dhanapalaratnam, Roshan; Cappelen-Smith, Cecilia; Thomas, Peter; Beran, Roy G
Abstract : Introduction: Noting a perceived increased case-load of Creuzfeldt-Jakob disease (CJD) patients at Liverpool Hospital, in the South-Western Sydney Local Health District (SWSLHD), the authors questioned the accepted death from CJD incidence of 1 per million. Methods: We reviewed the District Health-Information-Exchange (HIE) database for all admissions with CJD diagnoses in SWSLHD hospitals, over a 5-year period 2014–2018. The SWSLHD services a population of 1, 001, 437. The HIE identified cases were reviewed according to World Health Organization (WHO) diagnostic criteria as used by the Australian national CJD registry. Definite and probable CJD cases were included in the study. Incidence per year was calculated from the final case number across the 5-year SWSLHD population. Results: 26 patients coded with a diagnosis of CJD were identified from HIE database over the period. These cases were critically reviewed and 20 confirmed as definite (n=4) or probable CJD (n=16) cases. The diagnoses of excluded patients (n=6) were herpes simplex encephalitis, paraneoplastic encephalitis, delirium, and 2 with progressive multifocal leukoencephalopathy. Calculated incidence based on 5-year SWSLHD population was 4.16 cases per 1 million population/year. Conclusions: In the 5-year period, we note an incidence of definite and probable CJD cases in the SWSLHD population, four times the national and worldwide reported rates. Cases from the last 2-months of 2018 are pending at the time of submission, which may alter these observations. These findings most likely represent a cluster of cases in the SWSLHD area but may alternatively reflect either better recognition or increased incidence of CJD.